A critical analysis of the degree of conversion of resin-based luting cements (Journal of Applied Oral Science, 2010)
OBJECTIVE: This study analyzed the degree of conversion (DC%) of four resin-based cements (All Ceram, Enforce, Rely X ARC and Variolink II) activated by two modes (chemical and dual), and evaluated the decrease of DC% in the dual mode promoted by the interposition of a 2.0-mm-thick IPS Empress 2 disc. MATERIAL AND METHODS: In the chemical activation, the resin-based cements were prepared by mixing equal amounts of base and catalyst pastes. In the dual activation, after mixing, the cements were light-activated at 650 mW/cm² for 40 s. In a third group, the cements were light-activated through a 2.0-mm-thick IPS Empress 2 disc. The DC% was evaluated in a FT-IR spectrometer equipped with an attenuated total reflectance crystal (ATR). The data were analyzed by two-way ANOVA and Tukey's HSD test. RESULTS: For all resin-based cements, the DC% was significantly higher with dual activation, followed by dual activation through IPS Empress 2, and chemical activation (p